Coupling coordination degree of healthcare resource supply, demand and elderly population change in China - Mengyuan Ma; Leiyu Shi; Wanzhen Xie; Qiuli Zhu; Junqing Luo; Shengwu Liao; Oudong Xia; Gang Sun (BMC, 2024)
Abstract Object To analyze the trend of the coupling and coordination of the supply and demand of healthcare resources between the elderly population and healthcare resources in China during the period of 2012-2022, to reveal the impact of the growth of the elderly population on the relationship between the supply and demand of healthcare resources, and to put forward suggestions to improve the coupling and coordination between the supply and demand of healthcare resources and the elderly population, in order to cope with the challenges of an aging society. Methods By obtaining relevant data from authoritative data sources such as China Statistical Yearbook, Health and Health Statistics Yearbook, and the Chinese government website from 2012 to 2022, we constructed a comprehensive measurement index for the three systems of elderly population, healthcare resource supply, and healthcare resource demand; Using the entropy value method to assign weights to the indicators, combined with the coupling coordination degree model, to reveal the changes of the elderly population change and the supply and demand of medical and health resources; using ArcGIS technology, to study the spatial characteristics of the elderly population change and the supply and demand of medical and health resources. Results From 2012 to 2022, the supply and demand of healthcare resources and the variation of the elderly population in China show a continuous growth trend, and the comprehensive development level of the system gradually climbs from a low level to a high level. The fluctuation of coupling degree and coordination degree rises, although the coordination degree has always been lower than the coupling degree, but the distance between the coordination degree and the coupling degree gradually narrows with the passage of time. The coordination degree between population aging and medical and health resources development shows spatial heterogeneity in China, with the eastern region significantly higher than the western region/. Conclusions The coupling degree between population aging and healthcare resource supply and demand in China from 2012 to 2022 shows a general upward trend from low coupling to medium-high coupling, but it is worth noting that even though the degree of coupling increases, the degree of coordination is still relatively lagging behind, suggesting that the government and relevant departments need to pay more attention to coordinated allocation and management of healthcare resources. At the same time, the spatial differences in the degree of coordination among provinces suggest that future policymakers should take regional differences into full consideration in policymaking and sustainable development.